(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Sustainable development is launched through the interaction between the economy and natural resources and preserving them from exhaustion as well as the efficient management of natural and social resources and includes a diversified economic condition and thus is the focus of attention to the development of economic structures, which is intended to improve the level of human well-being by increasing its share in the necessary goods and services and their relationship With economic growth, which is the most important driver of economic transformation, because it reflects the ability of society and increasing its productive capabilities and investing in the optimal way Although the Iraqi economy is considered one of the diversified economies because of its important natural, agricultural and human resources, it still suffers from structural imbalances in what its various sectors contribute to the gross domestic product, as the extractive sector continues to control the largest part, and the oil revenues formed the section The greatest of Iraq’s foreign exchange earnings due to the decline and modest growth rates of other sectors. The public sector is the main engine for economic development, while the private sector has a limited role and has not had the opportunity to implement major investments.